Hearing Health Awareness among Medical Practitioners Managing Patients with Diabetes in South Africa - Jinabhai, Divaksha (Department of Health and Rehabilitation Sciences, 2024)
Background. Research has shown that auditory symptoms can occur as diabetes mellitus (DM) related complications. DM related auditory symptoms can include hearing loss (HL), tinnitus and balance disorders. The negative impact of DM on hearing health in context of the rise in the prevalence of DM, lends impetus for audiological assessment and management of patients with diabetes (PWD). It is unknown as to whether medical practitioners (MPs) managing PWD are aware of DM related auditory symptoms and in turn counsel and refer PWD for audiological assessment and management. Aim and Objectives. The study had four aims and several objectives per aim. The first aim was to determine South African MPs' awareness of DM related auditory symptoms. The objectives for this aim included determining the proportion of MPs who are aware of DM related auditory symptoms, which DM related auditory symptoms MPs are aware of and how MPs became aware of the symptoms. The second aim was to determine whether MPs refer for DM related auditory symptoms and the objective to achieve this aim was to determine the proportion of and reasons for DM related auditory symptom referrals. The third aim was to investigate the relationship between awareness of and referral for DM related auditory symptoms among MPs. The objectives for this aim included investigating if there is a correlation between awareness of and referrals for DM related auditory symptoms and referrals of PWD and determining if MPs years of experience influenced awareness of and referrals for DM related auditory symptoms. The fourth and last aim of the study was to describe counselling practices of MPs on DM related auditory symptoms. The objectives for this aim were to determine whether information regarding DM related auditory symptoms is included in counselling sessions, MPs' familiarity on the audiologist's role in the management of DM related auditory symptoms and the relationship between MP's familiarity with the role of an audiologist and counselling on DM related auditory symptoms. Research design. The study employed a descriptive cross sectional survey design. Purposive sampling was utilised, and prospective participants were recruited online through the data bases of various medical associations in South African as well as social media. An 18-item online survey questionnaire was designed for this study, covering A) demographic details B) awareness of DM related auditory symptoms and C) referral information. The survey questionnaire was content validated and piloted prior to the main data collection. Data collection was facilitated online through SurveyMonkey™, over a four-and-a-half-month period. Data was analysed quantitatively using descriptive and non-parametric methods as well as qualitatively using content analysis. Results. A total of 379 participants consented to contribute to the survey and 236 responses were eligible for use in analysis. Most participants (n=46; 12.1%) were excluded for non-completion. Of the 236 participant responses analysed, majority were unaware (n=141; 59.7%) of, did not refer (n=119; 51.5%) for and never counselled (n=148; 65%) on DM related auditory symptoms. Majority of participants (n=102, 44.9%) were not at all familiar with the role of audiologists in the management of PWD. With participants who were aware of DM related auditory symptoms (n=95, 40.3%), there was an increased likelihood to refer PWD to an audiologist and/or ENT (p<0.001). Furthermore, counselling on DM related auditory symptoms was found to be significantly dependent on participant's familiarity with the role of audiologists in DM management (p<0.001). Conclusion. A high proportion of MPs were unaware of and do not refer or counsel PWD for DM related auditory symptoms. It was also found that majority of MPs were unaware of the role of audiologists in DM management. The findings of the study suggest the need to promote awareness surrounding DM related auditory symptoms among South African MPs, which in turn could improve management of DM related auditory symptoms in PWD. In addition, the study underscores the need to promote the multidisciplinary collaboration between audiologists and MPs in the management of PWD.